Adhesion of Nongerminated Botrytis cinerea Conidia to Several Substrata - Doss, Robert P. (1993)
Conidia of the plant pathogenic fungus Botrytis cinerea adhered to tomato cuticle and to certain other substrata immediately upon hydration. This immediate adhesion occurred with both living and nonliving conidia. Adhesion was not consistently influenced by several lectins, sugars, or salts or by protease treatment, but it was strongly inhibited by ionic or nonionic detergents. With glass and oxidized polyethylene, substrata whose surface hydrophobicities could be conveniently varied, there was a direct relationship between water contact angle and percent adhesion. Immediate adhesion did not involve specific conidial attachment structures, although the surfaces of attached conidia were altered by contact with a substratum. Freshly harvested conidia were very hydrophobic, with more than 97% partitioning into the organic layer when subjected to a phase distribution test. Percent adhesion of germinated conidia was larger than that of nongerminated conidia. Evidence suggests that immediate adhesion of conidia of B. cinerea depends, at least in part, on hydrophobic interactions between the conidia and substratum.